2009
DOI: 10.1542/peds.2008-2969
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Deformational Plagiocephaly

Abstract: Although previous studies have argued for both environmental and underlying biological factors associated with DP, we found that lateralization in children with DP could be largely explained by environmental factors such as sleep position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…There have also been some debated studies that show neonatal infants with postural asymmetries have a preference for spontaneously turning the head to the right when lying supine, but this does not occur in premature infants in weeks after birth. 14 Treatment options include observation, positioning, helmet or sock hat therapy, and surgery. Surgery is usually not warranted in DP.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been some debated studies that show neonatal infants with postural asymmetries have a preference for spontaneously turning the head to the right when lying supine, but this does not occur in premature infants in weeks after birth. 14 Treatment options include observation, positioning, helmet or sock hat therapy, and surgery. Surgery is usually not warranted in DP.…”
Section: Discussionmentioning
confidence: 99%
“…56 Others have pointed out that head asymmetry eventually improves with time and seldom worsens beyond 4 months, 16,45,50,52,56,69 suggesting that watchful waiting rather than invasive surgery is a more reasonable option. However, the more recent evidence indicates that the deformity may not improve after 15 months of age, 24,32,40,48,61,64 which brings to the table another highly controversial issue surrounding PP. Another argument proposed for surgical adjustment involved those who are referred at a later age when remodeling of the skull is no longer possible.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Concerns about head shape were common, particularly at 4 months. Some studies [13,20,30] have shown that twins are at greater risk of developing plagiocephaly, probably due to increased exposure to risk factors such prematurity and in utero compression. In our group of twins, it is of note that with increasing age, concerns about deformational plagiocephaly were significantly more likely in Twin 1 than in Twin 2, confirming an earlier finding that the lower in utero twin is at increased risk for deformational plagiocephaly [18].…”
Section: Breastfeedingmentioning
confidence: 99%